Role of exosomal ncRNAs in traumatic brain injury - Ozal Beylerli; Rasim Tamrazov; Ilgiz Gareev; Tatiana Ilyasova; Alina Shumadalova; Yunlong Bai; Baofeng Yang (Non-coding RNA Research, 2023)
Traumatic brain injury (TBI) is a complex neurological disorder that often results in long-term disabilities, cognitive impairments, and emotional disturbances. Despite significant advancements in understanding the pathophysiology of TBI, effective treatments remain limited. In recent years, exosomal non-coding RNAs (ncRNAs) have emerged as potential players in TBI pathogenesis and as novel diagnostic and therapeutic targets. Exosomal ncRNAs are small RNA molecules that are secreted by cells and transported to distant sites, where they can modulate gene expression and cell signaling pathways. They have been shown to play important roles in various aspects of TBI, such as neuroinflammation, blood-brain barrier dysfunction, and neuronal apoptosis. The ability of exosomal ncRNAs to cross the blood-brain barrier and reach the brain parenchyma makes them attractive candidates for non-invasive biomarkers and drug delivery systems. However, significant challenges still need to be addressed before exosomal ncRNAs can be translated into clinical practice, including standardization of isolation and quantification methods, validation of their diagnostic and prognostic value, and optimization of their therapeutic efficacy and safety. This review aims to summarize the current knowledge regarding the role of exosomal ncRNAs in TBI, including their biogenesis, function, and potential applications in diagnosis, prognosis, and treatment. We also discuss the challenges and future perspectives of using exosomal ncRNAs as clinical tools for TBI management.